ACUTE LIMB ISCHEMIA: AN UPDATE ON DIAGNOSIS AND MANAGEMENT - Sebayang, Abed Nego Okthara (Essential: Essence of Scientific Medical Journal, 2021)
Acute Ischemic Limb (ALI) is a condition in which there is a sudden decrease in perfusion of stool caused by thrombus and embolism. The thrombus in question is derived from the development of arterial disease, aortic dissection, thrombus graft, aneurysm, hypercoagulability, iatrogenic and other.This review presents an update on the diagnosis and management of acute limb ischemia (ALI), a severe condition associated with high mortality and amputation rates. A comprehensive spectrum of ALI etiology is presented, with highlights on embolism and in situ thrombosis. The steps for emergency diagnosis are described, emphasizing the role of clinical data and imaging, mainly duplex ultrasound, CT angiography and digital substraction angiography. The different therapeutic techniques are presented, ranging from pharmacological (thrombolysis) to interventional (thromboaspiration, mechanical thrombectomy, and stent implantation) techniques to established surgical revascularization (Fogarty thrombembolectomy, by-pass, endarterectomy, patch angioplasty or combinations) and minor or major amputation of necessity. Postprocedural management, reperfusion injury, compartment syndrome and long-term treatment are also updated